University social responsibility or social extension? Elements for an analysis of universities social commitment (2020)
In the year 2008, the University of Ibagué launched several initiatives to articulate higher education with local development. The Programa Paz y Región (Peace and Region Program) is one of those initiatives and it is the focus of this article, whose purpose is to analyse this program in the light of two related concepts: university extension programmes and social responsibility (SR). Our analysis is based on a managerial perspective and our hypothesis is that “Paz y Región” responds to regional development in Tolima, Colombia, from a co-constructed perspective of extension programmes.